Diálogos Freireanos: A Educação E Formação De Jovens E Adultos Em Portugal E No Brasil
DOI: 10.14195/978-989-26-1326-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Educação, Corpo, Cultura: caminhos possíveis para a Humanização e a Educação de Jovens e Adultos

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The correlations between Mexico and Brazil in the field of technical and professional education have been the object of our research since 2014. In our studies (Silva, 2014, 2017, 2018a, 2018b, 2019; Silva and Riboli, 2016), we have found out that both countries have suffered great influence from the proposals of international organizations, which, in turn, have not imposed their educational perspectives from the top down. They have acted through partnership with national institutions to implement their proposals.…”
Section: Relations Between Brazil and Mexicomentioning
confidence: 82%
See 2 more Smart Citations
“…The correlations between Mexico and Brazil in the field of technical and professional education have been the object of our research since 2014. In our studies (Silva, 2014, 2017, 2018a, 2018b, 2019; Silva and Riboli, 2016), we have found out that both countries have suffered great influence from the proposals of international organizations, which, in turn, have not imposed their educational perspectives from the top down. They have acted through partnership with national institutions to implement their proposals.…”
Section: Relations Between Brazil and Mexicomentioning
confidence: 82%
“…In addition to the OECD, another major influencer of public policy in Brazil and Mexico has been the World Bank. In surveys carried out in 2015 and 2016, Silva and Riboli (2016) analyzed 50 projects financed by the World Bank, between 1974 and 2016, in both Mexico and Brazil. According to the results of the analysis, most Brazilian projects were aimed at structuring and improving the education systems of the states, with an emphasis on the processes of training teachers and school management teams, improving basic education and the infrastructure of schools.…”
Section: Relations Between Brazil and Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Creation of the foundations of a concept or model that supports this practice" (LB89); 6. "Promote training workshops given by leading professionals in the area with the main objective of reinforcing knowledge and promoting training and autonomous production in stages after training, so that collective creations and artistic construction as a whole take place in a logic of sharing where everyone can be part of the artistic-cultural whole" [36](p. 8) (LP17).…”
Section: Resultsmentioning
confidence: 99%
“…Essa iniciativa, apregoada pelo MEC, eliminaria a necessidade de prover a EJA no país (SILVA, 2005), a qual passou a ser conduzida por mais um programa, dessa vez, dirigido por organização não-governamental, Alfabetização Solidária, da ex primeira dama D.…”
Section: Introductionunclassified